KEBERSATUAN HAMBA DENGAN TUHAN: Perdebatan antara Pemikiran Hamzah Fansuri dan Nuruddin Al-Raniry - Musarofah, Siti (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
This literature review research, aims to understand the thoughts of Hamzah Fansuri and Nurruddin al-Raniry about the unity of the soul or human life (servant) with God, after death. Through the literary reception method approach, researchers use manuscripts Sharâbbu’L-‘Âshiqîn, Asrâru’L-‘Âifîn, and al-Muntahi written by Hamzah Fansuri and Asrâr al-Insân written by Nurruddin al-Raniry as the main data source, the situation of the researcher when reading the literary text was already equipped with knowledge of other texts, which discussed the two literary texts, so that is directs the content of the reading texts.The results of this study include: 1) according to Hamzah Fansuri the ruh of human after being separated from the body (dead), will reunite with the Dhat of Allah because according to Hamzah, the ruh of human comes from God through the process tajalli (emanasi). Meanwhile, according to Nur al-Din al-Raniry the ruh of human after death will taraqqi up to the first sky until the ninth sky in accordance with the degree of goodness in the world. Ruh of mu’min will taraqqi up to the first sky, ruh of ‘abid (worship expert) will taraqqi up to the second sky, ruh of zahid (the zahid peoples) will taraqqi up to the third sky, ruh of ma’rifat expert will taraqqi up to the fourth sky, ruh of the trustees will taraqqi up to the fith sky, ruh of the Prophets will taraqqi up to the sixth sky, ruh of the murassal (the apostles of Allah) will taraqqi up to the seventh sky ruh of wali al-‘azm will taraqqi up to the eighth sky, ruh of the khatam al-Nabi (salla Allah alayhi wasallam) (Muhammad Saw) will taraqqi up to the ninth sky. This opinion is a rejection of Hamzah’s opinion that the ruh of mortal man will be united with God’s Dhat.",